The European network staff eXchange for integrAting precision health in the health Care sysTems (ExACT): a Marie Curie Research and Innovation Staff Exchange (RISE) project - Stefania Boccia; Roberta Pastorino; Marco Mariani; Walter Ricciardi (Epidemiology, Biostatistics and Public Health)
No Abstract